PELAKSANAAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH PERIODE 2019-2024 DI KABUPATEN BARRU - Syam, Faizal Tanjung; Usman, Jaelan; Hamrun, Hamrun (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the implementation of the legislative function of the Barru Regency Regional People's Representative Council for the 2019-2024 period. This research uses a qualitative approach with a descriptive type. The research sources consist of primary data, namely in-depth interviews. Research data was collected by participant observation. The results of this research show that the formation of Regional Regulations includes, among other things, four stages, consisting of; Review stage, planning stage, discussion stage, and validation stage. From the research results, it was also found that in the process of the legislative function of the DPRD during 2019-2024 there was a setback where the DPRD became increasingly passive. The right to initiative is reduced until it is not used at all. However, the process of implementing its legislative function has been carried out in accordance with applicable laws and regulations. However, there are still obstacles that affect the legislative function of the DPRD, including inadequate human resources, delays in the process of forming the Draft Regional Regulations, and lack of community involvement.